Polygamy in Islam: The Truth Unveiled - Nazia Fayaz Azad; Iqra Firdous; Bilal Ahmad (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
Marriage in Islam is a sign of god’s power and glory. The Quran says: “From his signs is that He has created for you spouses from yourselves that you may get peace and tranquility through them; He placed between you love and mercy. In these are signs for the people who reflect”. Islam did not invent the system of polygamy. It existed long before Islam came into the scene of world events. When it came into world scene in the seventh century of the Common Era, it inherited the existing marriage system. It is to the credit of Islam that it modified and reformed the system in existence at the time firstly by limiting the number of wives a person could have at a time i.e. four and secondly it put stringent conditions on a person who wanted to marry a second wife like his ability to maintain and provide for the family, to be fair and just to both the wives and so on. Islam is a practical religion; its laws are in line with human nature. It does not deny natural forces in humans; rather it confronts them and provides guidance to control the peace in society. If a man wants to fool around, Islam will hold him responsible and tie him down to duties towards that second wife and her children. If we talk of western countries, almost all have forbidden polygamy but adultery is most rampant in these countries. Many married men have mistresses or are involved in extra-marital affairs resulting in higher divorce rates, broken families and children growing without fathers. This paper explores the concept of polygamy and rulings through the realm of Quran and Hadith. It also clears the misconception associated with the eleven marriages that our beloved Prophet Muhammad[1] (SAW) solemnized and it also brings to bear that how Islam has given clear guidelines on all kinds of relationships: monogamy to polygamy.   [1] The last messenger of Allah who brought Islam into existence